Case reportDoes “cerebellar liponeurocytoma” always reflect an expected site? An unusual case with a review of the literature - Karabagli, Pinar; Sav, Aydin; Pamir, Necmettin (Folia Neuropathologica, 2014)
A rare tumour, cerebellar liponeurocytoma, is classified into glioneuronal tumours under the 2000 World Health Organization (WHO) classification of tumours of the central nervous system. The current 2007 WHO classification, therefore, assigns grade II to the cerebellar liponeurocytoma. Tumours are predominantly localized in cerebellar hemispheres, and the second most common location is the vermis. To date, approximately 40 reported cases of cerebellar and 10 cases of supratentorial intraventricular liponeurocytoma have been reported. In this report, an unusual case of cerebellar liponeurocytoma was presented with extracerebellar location. In the future tumour classification, it should be considered that liponeurocytomas are not restricted only to the cerebellum, but they are located in supratentorial areas as well.